Complete and Partial Lesions of the Pyramidal Tract in the Rat Affect Qualitative Measures of Skilled Movements: Impairment in Fixations as a Model for Clumsy Behavior - Ian Q. Whishaw; Dionne M. Piecharka; Felicia R. Drever (Neural Plasticity)
Little is known about prenatal and perinatal brain injury resulting in subsequent clumsy behavior in children. One candidate motor system is the pyramidal tract. The tract traverses the entire central nervous system and, through direct and indirect connections to the brainstem and spinal cord sensory and motor nuclei, is involved in the learning and execution of skilled movements. Here, rats, either naive or pretrained on a number of motor tasks, were assessed for acute and chronic impairments following complete or incomplete pyramidal tract lesions. Postsurgery rats with complete lesions were impaired on the qualitative measures of limb aiming, supination, and posture. Impaired movements require fixations, complementary movements in different body segments. The impairment in fixations was manifest acutely and underwent no improvement with subsequent training/testing. The finding that complete and partial pyramidal tract lesions produce chronic impairment in fixations provides insight for understanding clumsy behavior in humans and its potential remediation via specific training in making fixations.